McQuail's Media and mass communication theory - McQuail, Denis (London : SAGE Publications, 2020)
Positive Psychology brings together a range of research and a comprehensive review of the more recent work and lessons learned since the founder's original vision of this field. Organised into five sections: An Introduction, Positive Experiences, Personality Processes, External Influences, and Applications, this text provides a thorough introduction to an interesting and challenging area in Psychology. With a final look at the future of Positive Psychology, and its potential to inform social change and how useful this knowledge can be when considering the well-being of entire societies, this text is an enlightening read and invaluable resources for students. Strongly guided by empirical work this text encourages the reader to think critically and go beyond the facts. Key features: Provides a framework for teaching and understanding global trends in Positive Psychology. Inclusion and a review of up-to-date research. Using storytelling and happiness's intrinsic appeal to foster interest in the methods we use to answer important questions in Positive Psychology. Online resources including student self-tests, an instructor test bank, and links to additional web content.
Keywords: elektronické knihy; electronic books; Communication and Media Studies -- Mass Communication Theory